Implementasi Algoritma Massey-Omura dan Algoritma Elias Delcta Code Pada Pengamanan dan Kompresi File Dokumen - Rosalina Manalu (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
The rapid development of information technology requires users to be more careful in maintaining data confidentiality and security so that data is not known or manipulated by other parties. Data security is very important for users, data security can be maintained by everyone. Cryptography is one of the security tools used to encode a document file. One of them is by using the Massey-Omura algorithm, which is an asymmetric cryptographic algorithm, so that it has different keys for encryption and decryption. In the process of sending data, it also requires the duration of sending files to not give an opportunity to data thieves by compressing the data or reducing the size of the file to be smaller without losing the contents of the document file, so the data exchange process can be shorter Data compression is a process where text, audio, and video files are transformed into compressed files with smaller data sizes but do not lose the actual information. This study discusses the type of lossless compression, so that files obtained from decompression will be identical to the original data. Elias Delta Code is a type of lossless compression. The performance parameters of this algorithm will be measured by Ratio of Compression (RC, Space Saving (SS) and compression time. Data used in the testing process is data that consists of several types of characters. In this discussion will include explanation, how to work, advantages and The author will also try to provide a review of ways to improve the security level of document files.